# Difference between revisions of "The Fibonacci sequence"

From HaskellWiki

CaleGibbard (talk | contribs) |
CaleGibbard (talk | contribs) |
||

Line 29: | Line 29: | ||

== A fairly fast version, using some identities == |
== A fairly fast version, using some identities == |
||

+ | <haskell> |
||

fib 0 = 0 |
fib 0 = 0 |
||

fib 1 = 1 |
fib 1 = 1 |
||

Line 37: | Line 38: | ||

f1 = fib k |
f1 = fib k |
||

f2 = fib (k-1) |
f2 = fib (k-1) |
||

+ | </haskell> |
||

== Fastest Fib in the West == |
== Fastest Fib in the West == |

## Revision as of 18:12, 12 March 2007

Implementing the fibonacci sequence is considered the "Hello, world!" of Haskell programming. This page collects Haskell implementations of the sequence.

## Contents

## Naive solution

```
fib 0 = 0
fib 1 = 1
fib n = fib (n-1) + fib (n-2)
```

## Canonical zipWith implementation

```
fib = 1 : 1 : zipWith (+) fib (tail fib)
```

## With scanl

```
fib = fix ((1:) . scanl (+) 1)
```

## With unfoldr

```
unfoldr (\(f1,f2) -> Just (f1,(f2,f1+f2))) (0,1)
```

## A fairly fast version, using some identities

```
fib 0 = 0
fib 1 = 1
fib n | even n = f1 * (f1 + 2 * f2)
| n `mod` 4 == 1 = (2 * f1 + f2) * (2 * f1 - f2) + 2
| otherwise = (2 * f1 + f2) * (2 * f1 - f2) - 2
where k = n `div` 2
f1 = fib k
f2 = fib (k-1)
```

## Fastest Fib in the West

This was contributed by wli

```
import System.Environment
import Data.List
fib n = snd . foldl fib' (1, 0) . map (toEnum . fromIntegral) $ unfoldl divs n
where
unfoldl f x = case f x of
Nothing -> []
Just (u, v) -> unfoldl f v ++ [u]
divs 0 = Nothing
divs k = Just (uncurry (flip (,)) (k `divMod` 2))
fib' (f, g) p
| p = (f*(f+2*g), f^2 + g^2)
| otherwise = (f^2+g^2, g*(2*f-g))
main = getArgs >>= mapM_ (print . fib . read)
```

## See also

Discussion at haskell cafe:

http://comments.gmane.org/gmane.comp.lang.haskell.cafe/19623